2005
DOI: 10.1021/ja0434533
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Intermediates in Cobalt-Catalyzed Hydroformylation Using para-Hydrogen-Induced Polarization

Abstract: para-Hydrogen-induced polarization methods are shown to enable the in situ detection of linear and branched monophosphine-containing intermediates during hydroformylation when Co(eta3-C3H5)(CO)2(PCy3) is the catalyst precursor. The NMR signal characteristics of the alkyl arms of these species provide direct evidence for the rapid interconversion of linear and branched cobalt alkyls prior to the CO insertion step. The observation of additional para-hydrogen-enhanced signals for the corresponding linear and bran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 19 publications
0
49
0
Order By: Relevance
“…The parahydrogen enhancement, in conjunction with extensive 13 C labelling experiments, allowed these intermediates to be fully characterised, and their reaction pathways determined. The authors also reported a similar study into hydroformylation using Co( 3 -C 3 H 5 )(CO) 2 (PCy 3 ), in which cobalt acyl intermediates with both linear and branched acyl substituents were detected, in addition to the corresponding aldehydes [87]. The enhancement provided by the parahydrogen was found to be transferred into the organic ligand framework, thus allowing the characterisation of intermediates which do not contain discrete hydride ligands, mirroring the contemporary development reported by Duckett et al in the field of hydrogenation catalysis (vide supra, Section 2.2).…”
Section: Studies Of Catalytic Hydroformylation With Parahydrogenmentioning
confidence: 88%
“…The parahydrogen enhancement, in conjunction with extensive 13 C labelling experiments, allowed these intermediates to be fully characterised, and their reaction pathways determined. The authors also reported a similar study into hydroformylation using Co( 3 -C 3 H 5 )(CO) 2 (PCy 3 ), in which cobalt acyl intermediates with both linear and branched acyl substituents were detected, in addition to the corresponding aldehydes [87]. The enhancement provided by the parahydrogen was found to be transferred into the organic ligand framework, thus allowing the characterisation of intermediates which do not contain discrete hydride ligands, mirroring the contemporary development reported by Duckett et al in the field of hydrogenation catalysis (vide supra, Section 2.2).…”
Section: Studies Of Catalytic Hydroformylation With Parahydrogenmentioning
confidence: 88%
“…The signal enhancements PHIP provides have been used extensively to detect elusive reaction intermediates based on metal dihydrides by NMR spectroscopy [6,7]. It has also been used to generate hyperpolarized organic molecules by hydrogenation of unsaturated substrates [5].…”
Section: Introductionmentioning
confidence: 99%
“…Each of the previously proposed steps in cobalt-catalyzed hydroformylation was confirmed by the detection of intermediates using para-hydrogen-induced polarization [8]. Thermodynamic parameters relevant to the phosphane-modified cobalt-catalyzed hydroformylation reaction were reported.…”
mentioning
confidence: 76%
“…The cobalt-catalyzed hydroformylation of 1-octene was investigated using bis{tri(3fluorophenyl)phosphane}hexacarbonyldicobalt and Co 2 (CO) 8 as precatalysts in supercritical carbon dioxide. The catalytic performance in scCO 2 was compared to the one in toluene as a conventional solvent.…”
Section: Hydroformylation In Supercritical Fluidsmentioning
confidence: 99%
See 1 more Smart Citation